Autistic traits as a potential confounding factor in the relationship between schizotypy and conspiracy beliefs. Issue 4 (4th July 2021) - Georgiou, Neophytos; Delfabbro, Paul; Balzan, Ryan
ABSTRACT: Background: Conspiracy Theories (CT) are complex belief systems that view the world as being manipulated by multiple actors collaborating in the pursuit of malevolent goals. Although culture, education and sociological factors have been implicated in their development, psychological factors are recognized as important. Certain individual differences, including schizotypy and cognitive processing style, have been shown to make some individuals susceptible to CTs. However, the finding that schizotypy often co-occurs with autism spectrum disorder raises a question as to the relative and potentially confounding role of autistic traits in increasing vulnerability to CT beliefs. Method: A total of 508 adults were recruited from an international online panel. The study included measures of conspiracy beliefs, schizotypy and autistic traits as well as measures of information searching and cognitive style. Results: The results confirmed that both autistic and schizotypy traits were positively associated with CT beliefs, but that schizotypy traits were the strongest predictor. Exploratory analyses of cognitive style measures indicated potential avenues for further investigation in relation in differences in cognitive processes that might underlie the development of CTs for in people with autistic traits as opposed to schizotypal traits. Limitations: The study was based on a self-report methodology and did not utilise a clinical sample. Conclusion: Both schizotypal and autistic traits are reliable predictors of conspiracy beliefs, but schizotypy appears to be the stronger predictor and that autistic traits are not a strong confounding factor in this relationship. However, autistic traits may pose an additional risk factor for CT beliefs.